2020
DOI: 10.1002/maco.202011774
|View full text |Cite
|
Sign up to set email alerts
|

The role of Cr atom in the early steam oxidation of Fe‐based alloys: An atomistic simulation

Abstract: This study employed the density functional theory to capture the atomic‐level dissociation processes of steam and investigate the ions migration on Fe(001) and FeCr(001) surfaces, revealing the role of Cr atom in the early oxidation. Various coadsorption structures with different steam‐derived species have been systematically examined to find the most energetically favored surface site. The results showed that the steam dissociation on the alloy surface underwent two steps. First, H2O molecule on the top site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Our previous work revealed that water molecules are dissociated on the surface and gain electrons from metal atoms, resulting in the oxidation of alloy. [10] Figure 3 shows the loss of electrons on the surface layer and subsurface layer of Fe and FeCr alloy during the initial oxidation (0-1000 ps). Figure 3a reveals that the charge of Fe atoms on the surface increases at a varying rate, which could be roughly divided into three stages.…”
Section: The Initial Chemisorption Reactions On the Surfacementioning
confidence: 99%
See 3 more Smart Citations
“…Our previous work revealed that water molecules are dissociated on the surface and gain electrons from metal atoms, resulting in the oxidation of alloy. [10] Figure 3 shows the loss of electrons on the surface layer and subsurface layer of Fe and FeCr alloy during the initial oxidation (0-1000 ps). Figure 3a reveals that the charge of Fe atoms on the surface increases at a varying rate, which could be roughly divided into three stages.…”
Section: The Initial Chemisorption Reactions On the Surfacementioning
confidence: 99%
“…[6][7][8][9] Considerable effort has been devoted to analyze the formation of oxide scale on FeCr alloys. [1,[10][11][12] Zhu et al [1] investigated the oxidation behavior of a ferritic-martensitic steel exposed to deaerated SCW at 560-650°C and 25 MPa by oxidation experiment, and the oxidation kinetics at different temperature was analyzed. Shen et al [13] conducted a detailed characterization of material microstructure formed on stainless steels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, developing the capability to predict the high-temperature oxidation kinetics of multi-component alloys is highly desirable and of great interest in many applications involving extreme environments. Although computational approaches using conventional analytical and physics-based simulations have made significant advancements in investigating high-temperature oxidation, they are usually only applicable for a given length/time scale [3][4][5][6] or specific oxidation-related phenomena [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%